War and Peace - King Vidor (1956)
Napolean turns his attention to Russia and, in so doing, causes hardship and gril on a vast scale. The personal stories of the many characters, love affairs, and philosophical quests are woven throughout this huge and detailed tapestry of 19th-Century Russian life.
Keywords: Drama, Romance, War